Students’ perceptions on the use of English vlog within Youtube to enhance speaking skills / Amira Mohamad & Aminabibi Saidalvi - Mohamad, Amira; Saidalvi, Aminabibi (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Video Blog (vlog) within YouTube is currently one of the most popular daily digital videos among youngsters. This study investigated students’ perceptions on the use of English vlog within YouTube to enhance speaking skills. The respondents were 59 fourth-year students from one of the universities in the southern region of Malaysia. Using a mixed method design, the study utilised a set of questionnaire as the main instrument and supported with interview questions. The questionnaire was distributed through Google form and later six of the respondents were randomly selected for interview sessions. The data was examined using descriptive and thematic analysis. The results showed that students have positive perceptions towards English vlog as vlog can enhance their speaking skills. The students perceived English vlog within YouTube offers many positive impacts towards students’ speaking improvement in the aspects of language learning and motivation. Interestingly, students perceived that they learn many new vocabularies, correct pronunciation, contextual words, and different slangs. Students also perceive that vlogging increase their motivation to speak in English. It is concluded that students perceive vlog within YouTube enhance speaking skills.